MicroRNAs in Lipid Metabolism and Atherosclerosis - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2014)
BACKGROUND: MicroRNAs (miRNA) are mediators of post-transcriptional gene expression that likely regulate most biological pathways and networks. The study of miRNAs is a rapidly emerging field; recent findings have revealed a significant role for miRNAs in atherosclerosis and lipoprotein metabolism.CONTENT: Results from recent studies demonstrated a role for miRNAs in endothelial integrity, macrophage inflammatory response to oxidized low-density lipoprotein, vascular smooth muscle cell proliferation and cholesterol synthesis. These mechanisms are all vital to the initiation and proliferation of atherosclerosis and cardiovascular disease. The importance of miRNAs has recently been recognized in cardiovascular sciences and miRNAs will likely become an integral part of our fundamental comprehension of atherosclerosis and lipoprotein metabolism. The extensive impact of miRNA mediated gene regulation and the relative ease of in vivo applicable modifications highlight the enormous potential of miRNA-based therapeutics in cardiovascular diseases.SUMMARY: miRNA studies in the field of lipid metabolism and atherosclerosis are in their infancy, and thus there is tremendous opportunity for discovery in this understudied area. The ability to target miRNAs in vivo through delivery of miRNA-mimics to enhance miRNA function, or antimiRNAs which inhibit miRNAs, has opened new avenues for the development of therapeutics for dyslipidemias and atherosclerosis, offers a unique approach to treating disease by modulating entire biological pathways. These exciting findings support the development of miRNA antagonists as potential therapeutics for the treatment of dyslipidaemia, atherosclerosis and related metabolic diseases.KEYWORDS: atherosclerosis, lipoprotein, HDL, miRNA